Epibenthic Assessment of a Renewable Tidal Energy Site - Emma V. Sheehan; Sarah C. Gall; Sophie L. Cousens; Martin J. Attrill (The Scientific World Journal)
Concern over global climate change as a result of fossil fuel use has resulted in energy production from renewable sources. Marine renewable energy devices provide clean electricity but can also cause physical disturbance to the local environment. There is a considerable paucity of ecological data at potential marine renewable energy sites that is needed to assess potential future impacts and allow optimal siting of devices. Here, we provide a baseline benthic survey for the Big Russel in Guernsey, UK, a potential site for tidal energy development. To assess the suitability of proposed sites for marine renewable energy in the Big Russel and to identify potential control sites, we compared species assemblages and habitat types. This baseline survey can be used to select control habitats to compare and monitor the benthic communities after installation of the device and contribute towards the optimal siting of any future installation.